2009
DOI: 10.1017/s0025315409000381
|View full text |Cite
|
Sign up to set email alerts
|

A morphometric analysis of the genus Terschellingia (Nematoda: Linhomoeidae) with redefinition of the genus and key to the species

Abstract: The cosmopolitan and often ecologically dominant genus Terschellingia (Nematoda: Linhomoeidae), with 38 nominal species, is taxonomically a problematic taxon. Its species show high morphological plasticity, possess few diagnostic characters and identification keys are lacking. A revision of the genus was carried out based on morphological and morphometric data from the literature and from observations of specimens collected in Cienfuegos Bay, Caribbean Sea, Cuba. The diagnosis of the genus Terschellingia is em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…trachygaster complex (De Oliveira et al., ). Given the paucity of diagnostic characters and the high morphological plasticity of most species of Terschellingia (Armenteros et al., ), an integrative approach to the taxonomy of this genus, combining multilocus molecular and dedicated morphological tools, is warranted.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…trachygaster complex (De Oliveira et al., ). Given the paucity of diagnostic characters and the high morphological plasticity of most species of Terschellingia (Armenteros et al., ), an integrative approach to the taxonomy of this genus, combining multilocus molecular and dedicated morphological tools, is warranted.…”
Section: Resultsmentioning
confidence: 99%
“…They were rinsed three times with sterile distilled water to remove DESS. Each specimen was mounted individually on a temporary slide and identified using diagnostic morphological characters (Armenteros, Ruiz‐Abierno, Vincx, & Decraemer, ) under a LEICA DM R research microscope at high magnification. Diagnostic features of P. pandispiculatus and Te.…”
Section: Methodsmentioning
confidence: 99%
“…The percentage occupied by the amphidial fovea was previously indicated as an interspecific morphological variation for Microlaimus by Armenteros, Vincx & Decraemer (2010) . Furthermore, Armenteros et al (2009) argued that morphometry could be used in studies of phylogenetic relationships. These authors also suggested the possibility of evaluating the relationship between morphological plasticity and ecological success in free-living marine nematodes, based on a model proposed by Hollander (2008) .…”
Section: Discussionmentioning
confidence: 99%
“…We detected relatively few species of nematodes (79) in Cienfuegos Bay, most of them belonging to the order Monhysterida due to the dominance of fine, muddy, sediments in the basin. Two genera of freeliving marine nematodes from this bay have been reported as new for science (Cienfuegia Armenteros, Vincx &Decraemer, 2009 andPseudoterschellingia Armenteros, Vincx &Decraemer, 2009). In this article we present the description of two new genera belonging to the families Xyalidae Chitwood, 1951 andMicrolaimidae Micoletzky, 1922a.…”
mentioning
confidence: 91%